Electroporation in the Rodent Embryonic Brain Using Whole Embryo Culture System. Issue 1 (3rd January 2017) - Kikkawa, Takako; Takahashi, Masanori; Osumi, Noriko
Abstract: This unit describes basic methods for mammalian whole embryo culture (WEC) using embryonic day 10.5 mouse embryos, including the preparation of high‐quality immediately centrifuged (IC) rat serum that is commonly used for WEC and is essential for normal growth and development of cultured mouse and rat embryos in vitro. An alternative protocol for different stages of rodent embryos is also introduced. Since embryos for WEC are dissected out of the uterus and manipulated under the microscope, one can overcome many of the difficulties of gene delivery encountered using in utero electroporation. A description for a gene transfer method to label neural stem/progenitor cells of the cortical primordium in a highly region‐specific manner is also included. © 2017 by John Wiley & Sons, Inc.